Hypertext and Hypermedia: An Overview - Ramaiah, Chennupati K (DESIDOC Journal of Library & Information Technology, 2002)
The historical developments of hypertext (HT), which is non-linear text or non-sequential writing, hypermedia (HM) and multimedia; types of HT systems; their general characteristics, advantages, disadvantages and limitations are overviewed in this paper. It also lists important HT systems and HM products, their storage and distribution patterns. Problems like disorientation, cognitive overhead, lack of presentation, rhetoric and construction of default paths are also discussed. http://dx.doi.org/10.14429/dbit.12.6.3070